2016
DOI: 10.1186/s40712-016-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pin profiles on the microstructure and mechanical properties of underwater friction stir welded AA2519-T87 aluminium alloy

Abstract: Background: AA2519-T87 is a new armour grade aluminium alloy employed in the fabrication of light combat military vehicles. Joining of this material using fusion welding processes, results in the formation of solidification defects like porosity, alloy segregation and hot cracking. In order to overcome the solidification related problems, solid state welding processes such as friction stir welding (FSW) can be used. Though the joining takes place below the melting temperature of the material, the thermal cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The joint configuration of 150 mm × 150 mm × 6 mm was used in the investigation. Form the previous investigation, the present authors found that the taper threaded tool was well suited for joining this material and thus it was used in this investigation (Sree et al, 2015b). The tool traverse speed was varied from 20 mm/min to 40 mm/min by keeping other parameters constant.…”
Section: Methodsmentioning
confidence: 99%
“…The joint configuration of 150 mm × 150 mm × 6 mm was used in the investigation. Form the previous investigation, the present authors found that the taper threaded tool was well suited for joining this material and thus it was used in this investigation (Sree et al, 2015b). The tool traverse speed was varied from 20 mm/min to 40 mm/min by keeping other parameters constant.…”
Section: Methodsmentioning
confidence: 99%
“…Forasmuch as the CO 2 cooling media causes higher cooling rate among other conditions, complete material flow is suppressed especially at the weld root and causes weak mechanical bonding. Additionally, excess cooling rate seems to lead to high contraction and separation of base metals [ 46 ]. The lower stirring action and weaker mechanical interlocking at lower area of stir zone are the main hypothesis for this material behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of WF-FSW, the water is liquid until 100 • C and absorbs heat with specific heat capacity that is smaller than the latent heat of evaporation of CO 2 , thus the cooling rate and cooling capacity of CO 2 is larger than water [45]. With AF-FSW, the specific heat capacity of the air is smaller than the specific heat capacity of water; consequently, the cooling rate and cooling capacity of water is larger than those of compressed air [46]. The recorded temperature by NT3 in both aluminum and steel side proved that the generated heat diffuses into the leading edge (LE) of the tool.…”
Section: Thermal Historymentioning
confidence: 99%
“…According to Figure 7, in the AP-FSW and RP-FSW processes, the welding area in the welded specimens increased with increasing the tool offset in the first and second passes. In the FSW process, the SZ is generally formed at the tool pin passage locus, and its width is approximately equal to the diameter of the tool pin [8,37,47,63,64]. In P-FSW techniques, in addition to the dimensions of the tool, the width of this area depends on the tool offset in the first and second welding passes.…”
Section: Surface Morphology and Macrographs Of Welding Specimensmentioning
confidence: 99%